Albumin binding, anticancer and antibacterial properties of synthesized zero valent iron nanoparticles - Sedaghat Anbouhi T (Dove Medical Press, 2018)
Tabassom Sedaghat Anbouhi,1,* Elnaz Mokhtari Esfidvajani,2,* Fahimeh Nemati,1 Setareh Haghighat,3 Soyar Sari,2 Farnoosh Attar,4 Arezoo Pakaghideh,5 Mohammad Javad Sohrabi,6 Seyyedeh Elaheh Mousavi,6 Mojtaba Falahati7 1Department of Biotechnology, Faculty of Advanced Science and Technology, Tehran Medical Sciences, Islamic Azad University, Tehran, Iran; 2Department of Cellular and Molecular Biology, Faculty of Advanced Science and Technology, Tehran Medical Sciences, Islamic Azad University, Tehran, Iran; 3Department of Microbiology, Faculty of Advanced Science and Technology, Tehran Medical Sciences, Islamic Azad University, Tehran, Iran; 4Department of Biology, Faculty of Food Industry and Agriculture, Standard Research Institute (SRI), Karaj, Iran; 5Department of Toxicology and Pharmacology, Faculty of Pharmacy, Pharmaceutical Science Branch, Islamic Azad University (IAUPS), Tehran, Iran; 6Department of Pharmacology, School of Medicine, Tehran University of Medical Sciences, Tehran, Iran; 7Department of Nanotechnology, Faculty of Advanced Science and Technology, Tehran Medical Sciences, Islamic Azad University, Tehran, Iran *These authors contributed equally to this work Background: Nanoparticles (NPs) have been emerging as potential players in modern medicine with clinical applications ranging from therapeutic purposes to antimicrobial agents. However, before applications in medical agents, some in vitro studies should be done to explore their biological responses.Aim: In this study, protein binding, anticancer and antibacterial activates of zero valent iron (ZVFe) were explored. Materials and methods: ZVFe nanoparticles were synthesized and fully characterized by X-ray diffraction, field-emission scanning electron microscope, and dynamic light scattering analyses. Afterward, the interaction of ZVFe NPs with human serum albumin (HSA) was examined using a range of techniques including intrinsic fluorescence, circular dichroism, and UV–visible spectroscopic methods. Molecular docking study was run to determine the kind of interaction between ZVFe NPs and HSA. The anticancer influence of ZVFe NPs on SH-SY5Y was examined by MTT and flow cytometry analysis, whereas human white blood cells were used as the control cell. Also, the antibacterial effect of ZVFe NPs was examined on Pseudomonas aeruginosa (ATCC 27853), Escherichia coli (ATCC 25922), and Staphylococcus aureus (ATCC 25923). Results: X-ray diffraction, transmission electron microscope, and dynamic light scattering analyses verified the synthesis of ZVFe NPs in a nano-sized diameter. Fluorescence spectroscopy analysis showed that ZVFe NPs spontaneously formed a complex with HSA through hydrogen bonds and van der Waals interactions. Also, circular dichroism spectroscopy study revealed that ZVFe NPs did not change the secondary structure of HSA. Moreover, UV–visible data presented that melting temperature (Tm) of HSA in the absence and presence of ZVFe NPs was almost identical. Molecular dynamic study also showed that ZVFe NP came into contact with polar residues on the surface of HSA molecule. Cellular assays showed that ZVFe NPs can induce cell mortality in a dose-dependent manner against SH-SY5Y cells, whereas these NPs did not trigger significant cell mortality against normal white bloods in the concentration range studied (1–100 µg/mL). Antibacterial assays showed a noteworthy inhibition on both bacterial strains. Conclusion: In conclusion, it was revealed that ZVFe NPs did not induce a substantial influence on the structure of protein and cytotoxicity against normal cell, whereas they derived significant anticancer and antibacterial effects. Keywords: zero valent iron, nanoparticle, spectroscopy, docking, anticancer, antibacterial activity